THE EFFECT OF PRODUCT QUALITY AND ELECTRONIC WORD OF MOUTH (e-WOM) ON PURCHASE INTEREST (CASE STUDY OF RAYS COFFEE, MAKASSAR CITY) - Muhammad Nur Dzaky Putra Basir; Andi Mustika Amin; Rahmat Riwayat Abadi; Nurhaedah Nurhaedah (Jurnal Manajemen, 2026)
Abstract: This study aims to analyze the influence of product quality and electronic word of mouth (e-WOM) on consumer purchasing interest at Kopi Rays in Makassar City. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 70 respondents who had visited Kopi Rays. The research instrument used a Likert scale and was analyzed using multiple linear regression methods using IBM SPSS software, accompanied by classical assumption tests, t-tests, F-tests, and coefficients of determination (R²). The results show that product quality has a positive and significant effect on consumer purchasing interest. Electronic word of mouth (e-WOM) also has a positive and significant effect on purchasing interest. Simultaneously, product quality and e-WOM have a significant effect on purchasing interest with a coefficient of determination (R²) of 0.886, which means that 88.6% of the variation in purchasing interest can be explained by these two variables, while the remaining 11.4% is influenced by other variables outside the study. Overall, this study confirms that consistent improvement in product quality and management of digital communication through positive e-WOM are important strategies in increasing consumer purchasing interest in Kopi Rays in Makassar City. Keywords: Product Quality, Electronic Word of Mouth (e-WOM), Purchase Intention, Multiple Linear Regression.Keywords: Product Quality, Electronic Word of Mouth (e-WOM), Purchase Intention, Multiple Linear Regression